g(x) = 3x2 – 5x + 14

find: f(g(x))

Step-by-step explanation:

f(x)=-3x-1

g(x)=3x²-5x+14

f(g(x))

f(3x²-5x+14)

3(-3x-1)²-5(-3x-1)+14

3(9x²+6x+1)+15x+5+14

27x²+18x+3+15x+19

f(g(x))=27x²+33x+22

The academic affairs council is the highest expert body processing academic affairs, as stipulated by the university statutes. specialist aaro häkkinen (educational policy) took pa...Read More

1 more answers

answer is a. p = 78step-by-step explanation:...Read More

1 more answers

here the answers ur welcome also plz mark as brainliest if someone else anwers...Read More

1 more answers

the answer would be the first one, the box plot will have its right tail longer than the left tail because a few exceptionally high prices make the distribution skewed to the right...Read More

3 more answers

no step-by-step explanation: answer...Read More

2 more answers

a=24; b=12step-by-step explanation: a/b=2: 1a=2b36/(1+2)=12b=12a=24...Read More

1 more answers

36step-by-step explanation: divide 48÷4=12multiply 12*3=36 that's your answer...Read More

1 more answers

- Which inequality is represented by the graph? Oy>2/3x+1 Oy<-2/3...
- HELp please and thank youuu...
- Use the cosine double-angle identity cos(2θ) = 2cos^2θ-1 to derive an...
- HELP 7TH GRADE...
- Please someone help me with this??...
- What is the graph? A) positive slope B) negative slope C)m=0. D) unde...
- Which of the following equations shows how the solution can be checked...
- The following list gives the number of pets for each of 10 students....
- Write a linear function f with the values f(-2) =8 and f(1)=-10. f(x)=...
- ^(5)-20x^(4)+20x^(3-)20x^(2)+20please solve!...